Generalized heaviside functions in the Colombeau theory context - Villarreal, Francisco [UNESP] (My University, 2012)
We defined generalized Heaviside functions for a variable x in ℝ n, and for variables (x, t) in ℝ n × ℝ m. Then study properties such as: composition, invertibility, and association relation (the weak equality). This work is developed in the Colombeau generalized functions context. © 2012 Texas State University - San Marcos.
Keywords: Distribution; Generalized function; Heaviside function